2017
DOI: 10.1177/1475921717703053
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial debonding detection in fiber-reinforced polymer rebar–reinforced concrete using electro-mechanical impedance technique

Abstract: For reinforced concrete structures, the use of fiber-reinforced polymer rebars to replace the steel reinforcement is a topic that is receiving increasing attention, especially where corrosion is a serious issue. However, fiber-reinforced polymer rebar–reinforced concrete always carries the risk of structural failure initiated from the debonding damage that might occur at the reinforcement–concrete interface. This study employed an electro-mechanical impedance–based structural health monitoring technique by app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
63
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 98 publications
(66 citation statements)
references
References 40 publications
(37 reference statements)
0
63
0
2
Order By: Relevance
“…The high variation in Figure 14 revealed that the values of these parameters in the BPE and CMR models are highly affected by both failure mode and stirrups. The parameters α β s r which were obtained from specimens with stirrups (R1-C1-20-Y, R2-C1- 16 Figure 16. The analytical curves that were obtained by using the parameters fitted to its experimental counterpart are represented by BPE and CMR models, and the analytical curves obtained by using the medians of parameter are represented by BPE* and CMR* Models.…”
Section: Bond Stress-slip Relationship Model Between Gfrp Bar and Stimentioning
confidence: 99%
“…The high variation in Figure 14 revealed that the values of these parameters in the BPE and CMR models are highly affected by both failure mode and stirrups. The parameters α β s r which were obtained from specimens with stirrups (R1-C1-20-Y, R2-C1- 16 Figure 16. The analytical curves that were obtained by using the parameters fitted to its experimental counterpart are represented by BPE and CMR models, and the analytical curves obtained by using the medians of parameter are represented by BPE* and CMR* Models.…”
Section: Bond Stress-slip Relationship Model Between Gfrp Bar and Stimentioning
confidence: 99%
“…Furthermore, while corroded steel bars display visible warning signals such as expanded volume which leads to crack of concrete (Al-Salloum et al, 2013), degraded GFRP bars do not show any signals, which impose great challenges for engineers to determine the degradation degree of GFRP bars inside GFRP-RC structures. Some effective non-destructive evaluation developed techniques (Li et al, 2016(Li et al, , 2017Jiang et al, 2017;Xu et al, 2018) for monitoring the initial bonding quality and long-term efficiency of the interfacial bonding between GFRP bars and concrete. However, so far, there has not been any relevant technology or method to monitor the tensile strength degradation of GFRP bars in practical service.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is very important to detect both sliding and debonding in RC in time to ensure its safety and determine its fitness for service. A number of sliding and debonding sensors have been developed with various sensing mechanisms, primarily including mechanical, electrical, and acoustic [ 1 , 2 , 3 , 5 , 6 , 7 ]. Acoustic emission (AE) is one of the most powerful tools to assess the integrity of the RC structure, which correlates the AE parameters with the localized changes inside the structure [ 5 ].…”
Section: Introductionmentioning
confidence: 99%